Designing and Delivering Business Ethics Teaching and Learning - Sims, Ronald R. (Journal of business ethics, 2006)
The recent corporate scandals in the United States have caused a renewed interest and focus on teaching business ethics. Business schools and their faculties are reexamining the teaching of business ethics and are reassessing their responsibilities to produce honest and truthful managers who live lives of integrity and ethical accountability. The authors recognize that no agreement exists among business schools and their faculties regarding what should be the content and pedagogy of a course in business ethics. However, the authors hold that regardless of one’s biases regarding the content and pedagogy, the effective teaching of business ethics requires that the instructor in designing and delivering a business ethics course needs to focus particular attention on four principal questions: (1) what are the objectives or targeted learning outcomes of the course? (2) what kind of learning environment should be created? (3) what learning processes need to be employed to achieve the goals? and (4) what are the roles of the participants in the learning experience? The answers to these questions provide the foundations for any business ethics course. The answers are major determinants of the impact of a business ethics course on the thinking of students and the views on the ethical and professional accountabilities and responsibilities of managers in the workplace.